Gender mainstreaming in law and legal education - Vujadinović Dragica (Anali Pravnog Fakulteta u Beogradu)
Political revolutions of the 18th and 19th century engendered an idea of universal equality. However, the American Declaration of Independence and the French Declaration of the Rights of Man and of the Citizen have not been gender sensitive documents. Women had to struggle for a long time in order to achieve visibility in laws and they did gain an equal right to vote in the USA only 144 years later and in France only 160 years after the issuing of these documents. Contemporary international and national law has greatly advanced from a gender equality point of view. However, gender sensitive legislation and implementation of legal norms has been far from widely accepted. Gender sensitive legal education of (future) legislators, lawyers, judges, and prosecutors has thus been of the utmost importance. First, the article offers theoretical clarifications and historical background analysis of a sense and purpose of gender mainstreaming. The achievements in international law and strategic documents concerning gender equality will be taken into consideration in the second chapter. The main focus will be on the meaning of and instruments for gender mainstreaming in legal education in Serbia as well as generally. Paradigmatic examples from judicial practice will also be presented.